Exploring Reading Attitudes, Reading Self-Efficacy, and Reading Proficiency in a Blended Learning Context Among EFL Learners - Marco Cancino; Nicol Gonzalez (National Research University Higher School of Economics, 2023)
Background. Affective variables such as second language (L2) reading attitudes (RAs) and L2 reading self-efficacy (RSE) have been regarded as factors which influence academic results in regular face-to-face reading instruction. Research has reported that although positive RAs among adolescents may decline as they go through school, they still engage in diverse formal and informal reading environments involving printed and/or digital resources. These attitudes can be impacted by the sudden change in the way instruction is delivered in blended learning contexts which emerged due to the Covid-19 pandemic. Purpose. The present study applied a mixed methods approach to explore the relationship between the L2 RAs, L2 RSE, and L2 reading proficiency (RP) of Chilean high school students in a blended-learning context. Method. A sequential explanatory mixed-methods design was adopted to gather data from 124 Chilean high school students. The quantitative data collection was carried out by means of two adapted surveys assessing RAs and RSE, while the reading section of the Preliminary English Test (PET) was administered to determine the RP of participants. The qualitative aspect of the study involved semi structured interviews with ten participants. Results. Participants displayed moderately positive levels of RA and RSE. Furthermore, a strong correlation was found between RAs and RSE, and RSE was significantly correlated with RP. Qualitative data analysis revealed that the  emergency remote teaching context during the pandemic affected student reading behaviour in relation to the attitudes towards recreational digital reading, and that teacher instruction can influence their RAs and RSE. Conclusion. It is essential for EFL teachers to nurture student L2 RSE by means of effective and consistent reading activities with increasing challenge that include synchronous and asynchronous learning. Since most participants preferred to complete reading tasks in a recreational digital setting rather than an academic digital one, teachers should incorporate academic reading activities which are more engaging and contextualised to student age and preferences to effectively use the synchronous and asynchronous time at their disposal in blended settings.